2014
DOI: 10.1007/s00449-014-1243-0
|View full text |Cite
|
Sign up to set email alerts
|

Production of manganese peroxidase and laccase in a solid-state bioreactor and modeling of enzyme production kinetics

Abstract: Lignin-modifying enzymes have various promising applications such as biobleaching, biopulping, the functionalization of lignocellulosic materials, the modification of wood fibers, the remediation of contaminated soil and effluents, as well as improvement of the enzymatic hydrolysis of lignocellulosic substrates. In this study, the production of laccase and manganese peroxidase (MnP) in solid-state cultivation was examined. Oat husks were used as an inexpensive substrate for the white-rot fungus Cerrena unicolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Moilanen et al [16] reported that the maximum MnP activity (340 nkat/g DM) occurred after 14 days of fermentation in a solid-state reactor with an internal conveyor, but their MnP activity stayed at almost the same level at 100 g-scale in plastic jars and 4 kg-scale in bioreactor cultivation. A similar study was carried out by Vivekanand et al [32] using a bioreactor that contained four circular aluminum trays, and the maximum MnP activity (1,339.0 ± 131.23 U/l) was obtained after 6 days of SSF by Aspergillus fumigatus VkJ2.4.5.…”
Section: Discussionmentioning
confidence: 99%
“…Moilanen et al [16] reported that the maximum MnP activity (340 nkat/g DM) occurred after 14 days of fermentation in a solid-state reactor with an internal conveyor, but their MnP activity stayed at almost the same level at 100 g-scale in plastic jars and 4 kg-scale in bioreactor cultivation. A similar study was carried out by Vivekanand et al [32] using a bioreactor that contained four circular aluminum trays, and the maximum MnP activity (1,339.0 ± 131.23 U/l) was obtained after 6 days of SSF by Aspergillus fumigatus VkJ2.4.5.…”
Section: Discussionmentioning
confidence: 99%
“…In order to carry out large-scale laccase production by SSF, culture parameters should be investigated at a large scale, and some adjustments are necessary. Moilanen et al (2014) found a change in laccase activity obtained for a large-scale laboratory culture [63]. Among the culture parameters, the water content is one of the key points for the scaling up of laccase production by SSF.…”
Section: Comparison Of Laccase Production From Lignocellulosic Agricumentioning
confidence: 99%
“…Soy medium also in this case supported a high expression of Rb5 bleaching activity. One of the efficient producer of VP activity was Cerrena unicolor PM170798, which is known as a very efficient producer of laccase [43], like many other C. unicolor strains [44].…”
Section: Production Of Lignin-modifying Peroxidasesmentioning
confidence: 99%